Separating Church and State: A History - Green, Steven K. (Religion and American Public Life, 2022)
In Separating Church and State, Steven K. Green, renowned for his scholarship on the separation of church and state, charts the career of the concept and helps us understand how it has fallen into disfavor today with many Americans. In 1802, President Thomas Jefferson distilled a leading idea in the Early American Republic and wrote of a wall of separation between church and state. That metaphor, has come down from Jefferson to twenty-first century Americans through a long history of jurisprudence, political contestation, and cultural influence. Separating Church and State traces the development of the concept of the separation of church and state, and Supreme Court's application of it in the law. Green finds conservative criticisms of a separation of church and state overlook the strong historical and jurisprudential pedigree of the idea. Yet, arguing with liberal advocates of the doctrine, he notes that the idea remains fundamentally vague and thus open to loose interpretation in the courts. As such, the history of wall of separation is more a variable index of American attitudes toward the forces of religion and state. Indeed, Green argues that Supreme Court's use of the wall metaphor has never been essential to its rulings. The contemporary battle over the idea of a wall of separation has thus been a distraction from the real jurisprudential issues animating the contemporary courts.